Modeling of sodium sulfur battery for power system applications - Hussein, Zahrul F. (Faculty of Electrical Engineering, 2007)

(untitled)
Sodium sulfur battery is an advanced secondary battery that is relatively new in power system applications. This paper presents the modeling and simulation of sodium sulfur battery used in power system applications such as for battery energy storage system and power quality custom devices. Several electrical battery models are reviewed and important factors to be considered in modeling the battery such as internal resistance, temperature effect, electromotive force and depth of discharge are discussed. Based on the available empirical data, the voltage-current behavior and characteristics of NAS battery are modeled in PSCAD/EMTDC software tool. The model is then used in simulation studies of power system applications utilizing NAS batteries.